THE EFFECT OF MILLING METHOD ON PROTEIN PROFILE IN SORGHUM (Sorghum bicolor L.) KD-4 VARIETY - Kendri Wahyuningsih; Lusy Rismayani; Endang Yuli Purwani; Irma Herawati (AGROINTEK, 2019)
Milling is of important process to improve nutritional and palatability of sorghum seeds for human consumption. This study investigated the effect of milling process on protein fraction of sorghum flour and the bran. The result showed that dry milled sorghum flour contained higher protein than those of wet milled sorghum flour, and the highest protein content was found on sorghum bran.  Dry-milled sorghum flour has protein fraction in albumin, globulin, kafirin and glutelin higher than those of wet-milled sorghum flour. Wet-millled sorghum flour contained high protein fraction in cross link kafirin and cross link glutelin.  Different of protein fractions noticed among the samples suggested that the samples contained different in amount of extractable protein and this was due to the differences in total protein.